1994
DOI: 10.1007/bf00201593
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular studies of 132 patients with galactosemia

Abstract: We evaluated 132 galactosemia patients for the Q188R (glutamine-188 to arginine) mutation in the human galactose-1-phosphate uridyltransferase (GALT) gene and for GALT activity in their hemolysates by a sensitive radioisotopic method. In those without any detectable GALT activity (GG), the Q 188R mutation constituted 67% of the alleles. In patients with detectable GALT activity (GV), only 16% of the alleles were accounted for by Q188R. In all patients who were homozygous for the Q188R mutation, no erythrocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 15 publications
5
35
0
Order By: Relevance
“…The Q188R mutation was selected for study because it accounts for 60-70% of the classic galactosemia alleles identified in Caucasian patients studied to date (26,27). Furthermore, it impacts a position only two codons from the presumed active site of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The Q188R mutation was selected for study because it accounts for 60-70% of the classic galactosemia alleles identified in Caucasian patients studied to date (26,27). Furthermore, it impacts a position only two codons from the presumed active site of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…10 p.Q188R also accounts for approximately 50 to 58% of the mutant alleles in Hispanics of Mexican ancestry. 29 The IVS2-2AϾG is rare but has been described in Hispanic populations and is …”
Section: ј-Cactgtctctcttctttctgtcaggggctcccacaggatcagaggctggggccaactmentioning
confidence: 99%
“…7,11,12 The incidence of transferase-deficient galactosaemia varies considerably between countries but has been estimated at 1 in 62 000 in a large human pan-ethnic study population. 13 Ireland is of particular interest in this context due to the existence within the population of an endogamous group, known as 'Travellers'.…”
mentioning
confidence: 99%